Molecular Interactions between Mecamylamine Enantiomers and the Transmembrane Domain of the Human α4β2 Nicotinic Receptor - Bondarenko, Vasyl (American Chemical Society, 2014)
[Image: see text] To characterize the binding sites of mecamylamine enantiomers on the transmembrane domain (TMD) of human (h) (α4)(3)(β2)(2) and (α4)(2)(β2)(3) nicotinic acetylcholine receptors (AChRs), we used nuclear magnetic resonance (NMR), molecular docking, and radioligand binding approaches. The interactions of (S)-(+)- and (R)-(−)-mecamylamine with several residues, determined by high-resolution NMR, within the hα4β2-TMD indicate different modes of binding at several luminal (L) and nonluminal (NL) sites. In general, the residues sensitive to each mecamylamine enantiomer are similar at both receptor stoichiometries. However, some differences were observed. The molecular docking experiments were crucial for delineating the location and orientation of each enantiomer in its binding site. In the (α4)(2)(β2)(3)-TMD, (S)-(+)-mecamylamine interacts with the L1 (i.e., between positions −3′ and −5′) and L2 (i.e., between positions 16′ and 20′) sites, whereas the β2-intersubunit (i.e., cytoplasmic end of two β2-TMDs) and α4/β2-intersubunit (i.e., cytoplasmic end of α4-TM1 and β2-TM3) sites are shared by both enantiomers. In the (α4)(3)(β2)(2)-TMD, both enantiomers bind with different orientations to the L1′ (closer to ring 2′) and α4-intrasubunit (i.e., at the cytoplasmic ends of α4-TM1 and α4-TM2) sites, but only (R)-(−)-mecamylamine interacts with the L2′ (i.e., closer to ring 20′) and α4-TM3-intrasubunit sites. Our findings are important because they provide, for the first time, a structural understanding of the allosteric modulation elicited by mecamylamine enantiomers at each hα4β2 stoichiometry. This advancement could be beneficial for the development of novel therapies for the treatment of several neurological disorders.